2013
DOI: 10.1175/jcli-d-12-00338.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Australasian Teleconnections and Implications for Paleoclimate Reconstructions

Abstract: The stationarity of relationships between local and remote climates is a necessary, yet implicit, assumption underlying many paleoclimate reconstructions. However, the assumption is tenuous for many seasonal relationships between interannual variations in the El Niño-Southern Oscillation (ENSO) and the southern annular mode (SAM) and Australasian precipitation and mean temperatures. Nonstationary statistical relationships between local and remote climates on the 31-71-yr time scale, defined as a change in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 76 publications
5
97
0
Order By: Relevance
“…We exclude lag relationships between each driver and rainfall, which are generally weaker . Relationships between precipitation and ocean-atmosphere processes can vary in strength over time (Gallant et al, 2013). We therefore use moving correlation windows (window length = 30 years) to assess statistically significant (p < 0.1) correlations for temporal stability.…”
Section: Reconstructionmentioning
confidence: 99%
“…We exclude lag relationships between each driver and rainfall, which are generally weaker . Relationships between precipitation and ocean-atmosphere processes can vary in strength over time (Gallant et al, 2013). We therefore use moving correlation windows (window length = 30 years) to assess statistically significant (p < 0.1) correlations for temporal stability.…”
Section: Reconstructionmentioning
confidence: 99%
“…Conversion of the proxy into a climatic variable can be achieved through regression or traditional inverse methods as is done with the widely used regional drought atlases (Cook et al, , 2010aPalmer et al, 2015). Nevertheless, in many cases the multivariate nature of proxy data, the presence of large uncertainties and limited spatiotemporal coverage in a calibration proxy network or nonstationary behavior between the proxy predictor and the climate predictand render regression and inversion challenging (e.g., Wilson et al, 2010;Lehner et al, 2012;Smerdon, 2012;Tingley et al, 2012;Coats et al, 2013a;Gallant et al, 2013;Evans et al, 2014;Konecky et al, 2014;Raible et al, 2014;Wang et al, 2014bWang et al, , 2015Konecky et al, 2016).…”
Section: Expectations Of Temporal or Spatial Consistency Betweenmentioning
confidence: 99%
“…Coats et al 2013 found that atmospheric forcing cannot account for the non-stationary teleconnection between tropical Pacific SSTs and 200 mb geopotential height. Gallant et al 2013 found significant variations through time in teleconnections on near-centennial timescales in model simulations forced by internal dynamics alone, but Batehup et al 2015 found that using multiple teleconnected regions minimizes any effects of non-stationarities. As these relationships cannot be assessed within the instrumental record, it is crucial to first evaluate CMIP5 models in the twentieth century when model output and observations overlap, and additionally test the teleconnections of the proxy sites that will be used in CFRs.…”
Section: Introductionmentioning
confidence: 99%